Analys av data från flyglaserscanning - Björn, Johan (SLU/School for Forest Management, 2008)
In forestry there are always needs of forest data to make good strategic decisions of different actions and economic winning. Usually this data gets from field-estimations made by forest workers with expensive costs and sometimes unsatisfied quality. StoraEnso Skog is a great forest company in Sweden and they have part of the responsibility of the forest own by Bergvik Skog. Bergvik Skog is owner of 1, 9 million hectares productive forest land. Both Bergvik and StoraEnso have great interest in new inventory techniques to get the important forest data. The company Foran Remote Sensing offers the opportunity with airborne laserscanning of forest and forest land. Foran got the mission of Bergvik and StoraEnso to laser scan Bergviks possession in Älvdalen, Dalarna. According to that Bergvik and StoraEnso has started a new handling strategy of how to do thinning forest and they developed a new thinning mould based on over height & numbers of stems. The purpose and goal in this study was to make a comparing between laser data and traditional field inventory from the same spots to perhaps see different results between the methods. A number of forest stands where chosen and became visited in field (spruce mostly). Different rates for features as over height, stand basal area and number of stems where collected. When the laser data was received it was made serial of regressions analyses of this material to see correlations between the features and to give a vision of maintenance of these forest stands according to witch technique that where chosen. It was shown that the correlations between the features was weak and couldn't show any strong connections. The results in the thinning mould between these techniques where a just little and forest maintenance would probably not be very different from each other. It where just a few forests stand that denoted from the others. This study shows promising results for airborne laser scanning in the opportunity to collect acceptable and god rates for the features of over height and number of stems being important in estimations of thinning needs at Bergvik Skogs forests ground. In other words this new technique with airborne laserscanning will work very well in the new thinning mould to StoraEnso Skog and will be in great use to planning and forest maintenance.